2017
DOI: 10.1002/mp.12005
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Issues related to external marker block placement for deep inspiration breath hold breast radiotherapy

Abstract: The RPM marker block can be placed on the breast for DIBH treatments; however, caution should be used regarding surface dose effects. The two-dot marker block should not be used for block tilts beyond 20°. Marker block placement at a middle or superior position on the breast results in the strongest correlation with chest wall position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
(22 reference statements)
3
14
0
Order By: Relevance
“…The measured vertical motion amplitudes were 14.75 ± 0.05 and 15.05 ± 0.05 mm (mean ± SD) for the NRS and TMB, respectively, when measured with the untilted surrogate. When tilting the surrogates, a larger tilt resulted in a larger measured amplitude, but similar for both surrogates; this has been previously reported for the TMB [16]. No significant differences between the surrogates were found in tracking performance, The NRS has a base with a diameter of 38 mm and reflective markers affixed on a stalk with 30 mm spacing between them, i.e., the same distance as on the TMB.…”
Section: Tracking Of the Respiratory Signalsupporting
confidence: 79%
See 3 more Smart Citations
“…The measured vertical motion amplitudes were 14.75 ± 0.05 and 15.05 ± 0.05 mm (mean ± SD) for the NRS and TMB, respectively, when measured with the untilted surrogate. When tilting the surrogates, a larger tilt resulted in a larger measured amplitude, but similar for both surrogates; this has been previously reported for the TMB [16]. No significant differences between the surrogates were found in tracking performance, The NRS has a base with a diameter of 38 mm and reflective markers affixed on a stalk with 30 mm spacing between them, i.e., the same distance as on the TMB.…”
Section: Tracking Of the Respiratory Signalsupporting
confidence: 79%
“…Several studies have shown that a surrogate/marker positioned on the xiphoid process or the sternum improved correlation to breast/thoracic wall compared to a position on the abdomen [11,17,21], in general the closer the surrogate is placed to the breast in cranio-caudal and lateral directions the better [8,16]. NRS' narrow base enabled positioning of the surrogate on the sternum at the level of the papilla.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the RPM block was placed on the patients' abdomen, midway between the xyphoid process and the umbilicus, and a 5 mm gating window was selected, as recommended by the RPM manufacturer and in recent works . The positioning of the fiducial block on the sternum or breast can result in improved DIBH reproducibility, but concerns are associated to the lateral block tilt and surface dose effects . A reduced gating window can also contribute to increase targeting accuracy, but there is the evidence that large errors in CW position can occur despite a small gating window .…”
Section: Discussionmentioning
confidence: 99%